2021
DOI: 10.1590/1807-3107bor-2021.vol35.0028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obturation technique using a new bioceramic sealer on the presence of voids in flattened root canals

Abstract: The aim of this study was to evaluate the filling ability of a new ready-to-use calcium silicate-based sealer using thermoplastic or single-cone technique in flattened root canals. Twenty-four flattened distal canals of mandibular molars with a buccolingual diameter 4 or more times larger than the mesiodistal diameter were selected. The root canals were prepared and filled (n = 12), according to the following techniques: thermoplastic or single-cone technique using Bio-C Sealer. The teeth were scanned using Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Nevertheless, many factors may influence voids' proportion, including the root canal filling technique (Figure 3), film thickness, flowability, and wettability. Void incidence has been reported to be greater within oval root canals, especially when this space was filled with CHC and especially when using the SC technique or cold lateral compaction [101,102]. Another study assessed the filling quality of five obturation techniques in oval-shaped root canals by using an optical numeric microscope, SEM, and energy-dispersive X-rays (EDX) [103].…”
Section: Obturation Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, many factors may influence voids' proportion, including the root canal filling technique (Figure 3), film thickness, flowability, and wettability. Void incidence has been reported to be greater within oval root canals, especially when this space was filled with CHC and especially when using the SC technique or cold lateral compaction [101,102]. Another study assessed the filling quality of five obturation techniques in oval-shaped root canals by using an optical numeric microscope, SEM, and energy-dispersive X-rays (EDX) [103].…”
Section: Obturation Qualitymentioning
confidence: 99%
“…Micro-CT has been suggested to be the most reliable technique to investigate the filling quality differentiating gutta-percha, sealer, and voids. This technique allows the evaluation of void/porosity incidence (apical, middle, or coronal thirds), and the identification Void incidence has been reported to be greater within oval root canals, especially when this space was filled with CHC and especially when using the SC technique or cold lateral compaction [101,102]. Another study assessed the filling quality of five obturation techniques in oval-shaped root canals by using an optical numeric microscope, SEM, and energy-dispersive X-rays (EDX) [103].…”
Section: Obturation Qualitymentioning
confidence: 99%
“…Micro-computed tomography (micro-CT) is used to analyze root canal filling techniques (9,17,18). However, most micro-CT studies for comparisons between obturation techniques used straight root canals (2,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…However, this study showed a high percentage void in AH Plus and EndoSeal without showing the tendency according to the type of sealer. Previous research has shown that the incidence of voids is higher in oval root canals, especially when using the single-cone technique [ 28 , 29 ]. This study showed that void was found to be more common in molars (50%, 23/46 teeth) than premolar (38.5%, 5/13 teeth) or anterior (30.7%, 4/13 teeth) teeth.…”
Section: Discussionmentioning
confidence: 99%